TYPOLOGIES OF INTERMEDIALITY IN MODERN LINGUISTICS: PROBLEMS AND PROSPECTS - Chaiun, Iryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The article explores the main approaches to the typology of intermediality as a phenomenon of contemporary culture, art, and linguistics. Intermediality, understood as the interaction and intersection of different semiotic systems has become an essential aspect of modern communication and textual analysis. The study highlights the challenges in classifying intermedial phenomena, including the fluidity of media boundaries, the complexity of constructing universal theoretical models, and the dynamic nature of interpretation across various disciplines. Special attention is given to the methodological difficulties associated with intermediality research, particularly the need for integrative approaches that combine linguistic, semiotic, cultural, and media studies perspectives. The article emphasizes the importance of developing comprehensive typological frameworks to better understand the mechanisms of intermedial interaction. Furthermore, the study outlines the prospects for advancing typological approaches, particularly their significance for interdisciplinary research and their integration into contemporary scholarly discourse. A systematic classification of intermediality models is proposed, and the necessity of expanding methodological tools for analyzing this phenomenon is substantiated. The findings suggest that further exploration of intermediality can contribute to a deeper understanding of meaning-making processes in multimodal communication, as well as foster new directions in linguistic and media studies. _______________ References: • Prosalova, V. A. (2010). Intermedialnist u systemi intertekstualnykh zviazkiv [Intermediality in the system of intertextual connections]. Actualni problemy ukrainskoi literatury i folkloru, (15), 12–18. [in Ukrainian] • Fesenko, V. I. (2014). Literatura i zhyvopys: intermedialnyi dyskurs: navchalnyi posibnyk [Literature and art: intermediate aspect: a textbook]. Kyiv: KNLU. [in Ukrainian] • Besson, R. (2014). Prolégomènes pour une défnition de l’intermédialité à l’époque contemporaine [Preliminaries for a definition of intermediality in the contemporary era]. HAL, 2–20. https://shs.hal.science/hal-01012325/ [in French] • Clüver, C. (2007). Intermediality and interarts studies. In Changing Borders: Contemporary Positions in Intermediality (pp. 19–37). Lund: Intermedia Studies Press. • Hansen-Löve, A. (1983). Intermedialität und Intertextualität: Probleme der Korrelation von Wort und Bildkunst [Intermediality and intertextuality: Problems of the correlation between word and visual art]. Wiener Slawistischer Almanach, 11, 291–360. [in German] • Schroter, J. (2011). Discourses and models of intermediary. CLCWeb: Comparative Literature and Culture, 13(3). http://docs.lib.purdue.edu/clcweb/vol13/iss3/ • Wolf, W. (2011). (Inter)mediality and the study of literature. CLCWeb: Comparative Literature and Culture, 13(3). https://doi.org/10.7771/1481-4374.1789